Development of an affinity sensor for Ochratoxin A - Heurich, Meike (Cranfield University, 2008)
Ochratoxin A is a contaminant in wine and known to be immunosuppressive and possibly carcinogenic. Therefore, the development of a rapid and sensitive method for field analysis is required for risk assessment and management. The work presented in this thesis reports the construction of a sensor platform capable of fulfilling these requirements. As a sensor platform, screen-printed thick film electrodes and microelectrodes on a silicone support were investigated for sensor development. As biological recognition elements, an antibody specifically binding ochratoxin A and a peptide receptor that was designed using computational modelling were examined. A disposable immunosensor for ochratoxin A was developed based on screen-printing technology. An indirect competitive immunoassay format was used on bare screen printed gold electrode (SPGE). The performance of this sensor was compared to carboxmethylated dextran (CMD) modified SPGE. Detection was performed by chronoamperometry monitoring the reaction of tetramethylbenzidine and hydrogen peroxide catalysed by horseradish peroxidase. The SPGE-based immunosensor achieved a detection limit of 100 ng L-1 and the CMD-modified SPGE immunosensor 10 ng L-1. The latter has been used for ochratoxin A determination in wine samples and was validated against standard HPLC and a commercial immunoassay test kit. Wine sample analysis involved the sample pre-treatment using immunoaffinity chromatography, electrochemical wine component characterisation and interference control. The immunosensor format was transferred to a gold microelectrode array based on a silicone support for the purpose of signal sensitivity enhancement and miniaturisation in the prospect of field analysis. Preliminary data showed the characterisation of the microelectrode array immunosensor construction and characterisation. Further optimisation is needed to establish a calibration curve with the required sensitivity. The second part of the work comprised the design of a peptide receptor for ochratoxin A using computational methods by screening de novo designed peptide libraries. An octapeptide (CSIVEDGL) and a 13-peptide (GPAGIDGPAGIRC) were selected for synthesis and affinity characterised for ochratoxin A recognition using a surface plasmon resonance biosensor (BiacoreTM). The peptide receptors showed good sensitivity for ochratoxin A of 10 μg L-1. Preliminary affinity characterisation resulted in KA = 63 mM-1 for the 13-mer peptide and KA = 84 mM-1 for the octapeptide, which appears to be binding with higher strength to ochratoxin A. The affinity values correspond to the binding score (binding energy) calculated by computational modelling. This work shows the potential of designing peptide receptors for small molecules (e.g. ochratoxin A) and suggests their application in affinity sensors for detecting ochratoxin A contamination.